Mille nnium Development Goals (MDGs) and Poverty Alleviation i n Rivers State: A Sociological Perspective (Global Journal of Human-Social Science, 2014)
The paper examined the eradication and/or reduction of poverty in Rivers State through the targets and indicators of MDGs objectives. The paper posited that through the institutional agencies in the state, MDGs one (1) and two (2) achieved up to 70% deliverables. The scenario analysis method was deployed in line with MDG assessment indicator framework which provided information and reference items to measure specific goals and progress in terms of poverty alleviation -(A 3 days training workshop held in Port Harcourt). The workshop dovetailed into syndicate groups were critical analysis and inputs were made by participants. The finding is that goal 1 and 2 achieved up to 70% success in alleviating poverty in the state through Rivers State Sustainable Development Agency (RSSDA), Rivers Microfinance Agency (RIMA) etc. The government has projected a more comprehensive reduction package come 2015.
Keywords: mdgs; poverty; alleviation; rssda; new response approach (NRA); rima